2023
DOI: 10.1002/mnfr.202200799
|View full text |Cite
|
Sign up to set email alerts
|

Pantethine Ameliorates Recognition Impairment in a Mouse Model of Alzheimer's Disease by Modulating Cholesterol Content and Intestinal Flora Species

Abstract: Scope As a natural dietary low‐molecular‐weight thiol, pantethine helps maintain brain homeostasis and function in Alzheimer's disease (AD) mice. The current study aims to investigate the protective effects and underlying mechanisms of pantethine on the mitigation of cognitive deficits and pathology in a triple transgenic AD mouse model. Methods and results Compared to control mice, oral administration of pantethine improve spatial learning and memory ability, relieve anxiety, and reduce the production of amyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
0
0
Order By: Relevance
“…In addition, CoA is a source of the 4'-phosphopantetheinyl prosthetic group present in the acyl carrier protein, which is required for fatty acid synthesis in biological systems [ 81 ]. Many studies have demonstrated that pantethine has anticatabolic properties in fatty acid synthesis and stimulates fatty acid oxidation [ 82 , 83 ]. Pantetheine has been used in humans as a lipid-lowering drug and dietary pantethine has also been shown to improve liver lipogenesis in laying hens [ 84 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CoA is a source of the 4'-phosphopantetheinyl prosthetic group present in the acyl carrier protein, which is required for fatty acid synthesis in biological systems [ 81 ]. Many studies have demonstrated that pantethine has anticatabolic properties in fatty acid synthesis and stimulates fatty acid oxidation [ 82 , 83 ]. Pantetheine has been used in humans as a lipid-lowering drug and dietary pantethine has also been shown to improve liver lipogenesis in laying hens [ 84 , 85 ].…”
Section: Discussionmentioning
confidence: 99%